Some Notes on Overshooting - Stefan Homburg (Zeitschrift für Wirtschafts- und Sozialwissenschaften, 1989)
Using two examples we have shown that large fluctuations in real exchange rates cannot normally be attributed to "overshooting" in the Dornbusch sense. We proposed to use the interest differential between to countries as a direct and reliable measure of the extend of overshooting. Observing that differential immediately reveals that the past appreciation of the dollar against the mark has hardly anything to do with overshooting. – – Anhand zweier Beispiele wird argumentiert, daß größere Änderungen des realen Wechselkurses kaum einem "overshooting" im Sinne von Dornbusch zugeschrieben werden können. Es wird vorgeschlagen, das Zinsdifferential zwischen zwei Ländern als direktes und verläßliches Maß für das overshooting zu verwenden. Durch Betrachtung dieses Zinsdifferentials wird sofort klar, daß die Dollaraufwertung von 1980 - 85 unmöglich auf ein overshooting zurückgeführt werden kann
Keywords: F31; 330; Exchange Rate; Overshooting; Wechselkurs; Overshooting